Structural Characterization of Polygonum divaricatum L. Polysaccharide and Its Inhibitory Effect on Lipopolysaccharide-Induced Inflammation in RAW264.7 Cells - CUI Yanyan, YUAN Yongxu, GUO Mingkun, HE Wenbing, LI Ming, PEI Shichun, LI Dajun (Shipin Kexue)
Objective: To explore the in vitro anti-inflammatory activity and action mechanism of a polysaccharide extracted from Polygonum divaricatum L. (PSPDL). Methods: The structure of PSPDL was characterized using high-performance gel permeation chromatography (HPGPC), high-performance liquid chromatography (HPLC), Fourier transform-infrared spectroscopy (FT-IR), X-ray diffraction (XRD), and nuclear magnetic resonance spectroscopy (NMR). The in vitro anti-inflammatory activity and action mechanism of PSPDL were investigated in lipopolysaccharide (LPS)-induced RAW264.7 cells. Results: PSPDL had a relative molecular mass of 59.475 kDa and consisted mainly of mannose (Man), rhamnose (Rha), glucuronic acid (GlcA), galacturonic acid (GalA), glucose (Glc), galactose (Gal), and arabinose (Ara), with a molar ratio of 1.69:4.95:1.04:21.79:19.01:31.68:19.84. PSPDL was an α-pyran polysaccharide containing (1→4)-α-D-Glcp linkage. PSPDL inhibited the release of inflammatory factors and related gene mRNA expression, ameliorated oxidative stress, down-regulated the protein expression levels of p38, p-p38, IκB-α, p65, and p-p65. Conclusion: PSPDL exhibited anti-inflammatory activity, perhaps by regulating inflammatory mRNA expression and modulating the mitogen-activated protein kinases/nuclear factor kappa B (MAPK/NF-κB) signaling pathway. This finding provides a scientific basis for the development and utilization of PSPDL resources.